Activated Carbon Paste Electrode for Voltammetric Determination of Butylated Hydroxyanisole - Pasaribu, Regina; Noviandri, Indra (MultiTech Publisher, 2023)
Butylated Hydroxyanisole (BHA) is an antioxidant with phenolic groups commonly added to food materials as an oxidative deterrent. According to The Acceptable Daily Intake (ADI), the permissible human consumption limit for BHA is very low. Therefore, having a sensitive and simple analytical method for BHA determination is important. In this study, we developed an activated carbon paste electrode (aCPE) for the voltammetric determination of BHA in food samples. Carbon paste electrode (CPE) was activated in 1 M H2SO4 solution in two steps: 10 cycles of cyclic voltammetry followed by immersion in 1 M H2SO4 solution for 30 seconds. The aCPE electrode had been used for BHA determination in food samples and the results were in good agreement with those of HPLC.